The peculiarities of using and reading of hydrogen breath test results with lactose load in young children and their mothers - S. I. Ilchenko; S. M. Nedelska; T. V. Mozheiko (Zaporozhye State Medical University, 2019)
Purpose of the work is to evaluate efficacy of using hydrogen breath test with nutritional lactose load among young children and their mothers and correlation of the test results with manifestation of functional gastrointestinal disorders in children. Materials and methods. Hydrogen breath test with nutritional lactose load, genetic marker C (-13910)T of the gene MCM6 investigation by buccal scraping, microbiological investigation of stool were carried out in 32 young children between 1 month and 2 years of age with different manifestations of functional gastrointestinal disorders. HBT was carried out in mothers of investigated children. Results. 18.8 % of children had positive HBT (lactose intolerance - LI), 31.2 % of young children had doubtful result (small intestinal bacterial overgrowth syndrome - SIBO). Positive results of HBT were received in 43.7% of cases, doubtful ones were received in 9.4 % of women among mothers of investigated children. Maximal level of hydrogen in children with LI is 45.5 (40.0-53.0) ppm, it has been fixed on the 180th (150-180) minute, that is likely later than in adults. Investigation of children intestinal microbiota showed decreasing of bifidobacteria and lactobacteria in 43.8% of cases and increasing of opportunistic flora in 93.8 % against this background including K. pneumoniae - 46.9 %, S. aureus - 53.1%, K. oxytoca - 18.8 %, E. Coli - 31.2 %, E. Faecalis - 6.2 %, E. Cloacae - 6.2 %, Clostridia - 9.4 %, C. freundi - 6.2 %. Almost all children (93.8 %) were carriers of the main allele C with equal relations (in 46.9 %) between the genotypes C/C and C/T and absence of significant correlation with results of HBT according to the investigation of lactase intolerance genetic marker C (-13910)T. Conclusions. The performed investigations have proved that associations of different opportunistic flora including S. aureus and K. pneumoniae on the background of decreasing of lactobacteria (50.0 %) with the high rate of functional diarrhea and intensity of manifestations of regurgitation syndrome, were revealed in many young children with SIBO (80.0 %) and LI (83.3 %). The lack of statistically significant correlations between the results of HBT in children and their mothers, as well as with genetic marker C (-13910) T of the gene MCM6 investigation demonstrates low level of information content of these investigations for the evidence of transient lactose intolerance in young children.